Pain perception in patients with hidradenitis suppurativa. (8th July 2019) - Nielsen, R.M.; Lindsø Andersen, P.; Sigsgaard, V.; Theut Riis, P.; Jemec, G.B.
Summary: Background: Pain is a prominent symptom of hidradenitis suppurativa (HS) and has been defined as a domain in the Core Outcome Set for the disease. Quality and intensity of pain is influenced by depression and anxiety, both of which are associated with HS. Objectives: To describe HS‐related pain quantitatively and qualitatively; and to investigate how disease severity, depression and anxiety correlate with self‐reported pain quality. Methods: Pain perception was investigated using the McGill Pain Questionnaire. Symptoms of depression and anxiety were examined using the Hospital Anxiety and Depression Scale. Statistical analyses investigated differences in number of words chosen (NWC) and pain‐rating index rank [PRI(R)] in patients with severe disease and in patients with depression/anxiety. Results: A total of 138 patients with HS were recruited in an outpatient clinic (October 2017–March 2018). Patients presented a median NWC of 11·5 and a PRI(R) of 59·0%. Most common descriptors were 'shooting' (83%), 'itchy' (79%) and 'blinding' (75%). Patients with depression or anxiety presented significantly higher PRI(R)s [depressed 65% vs. non‐depressed 57% ( P = 0·015); anxious 65% vs. nonanxious 57% ( P = 0·004)]. Patients with involvement of three or more HS regions vs. those with fewer than three involved regions exhibited a significantly higher NWC (13 vs. 8; P = 0·048). Conclusions: HS‐related pain includes nociceptive and neuropathic pain, and perception appears to be influenced by disease severity, anxiety and depression. A multimodal pain management strategy may be the most appropriate; however, more detailed studies are necessary to define recommendations on pain management. What's already known about this topic? Pain is a core outcome domain hidradenitis suppurativa. Few studies have addressed this significant clinical problem. What does this study add? This study suggests that HS pain comprises both nociceptive and neuropathic pain. Pain appears associated to depression, anxiety and severity of the disease. Abstract : Plain language summary available online Linked Comment:  Alhusayen. Br J Dermatol 2020; 182 :17–18 .